What’s the Problem with Product Obsolescence? Critical Policy Perspectives from Australia’s Right to Repair Inquiry - O’Neill, Morgan; Maguire, Rowena; Hurst, Bree; Walton, Andrea (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Extending product lifetimes is a critical aspect of achieving Circular Economy outcomes, however current policy discussions in Australia do not adequately address product obsolescence (PO). Using a problematisation analysis method, this research aims to uncover how PO is framed within Australia’s Right to Repair (R2R) Inquiry and how these problematisations impact the effective transition to a Circular Economy. The document analysis results indicate that Australian regulatory interventions shift responsibility for PO onto consumers, framing the issue as one of consumer choice driving rapid disposal. It was found that despite strong support for design stage interventions in submissions to the Inquiry, the report ultimately recommended against placing PO obligations on producers. Instead, the report suggested introducing labelling requirements, placing the burden of obsolescence on consumers. This framing reflects an ideology of economic rationalism, driven by governmental hesitancy to strongly regulate the private sector. In this representation, the environmental impacts of PO, and the importance of regulation in environmental conservation, are minimised. The Australian approach can be contrasted with the European Union approach which places responsibility on producers to design products in accordance with eco-design requirements and disseminate repairability information, emphasising the role of comprehensive policy mixes in driving positive environmental outcomes. The contrasts between these solutions reflect different understandings of not only what the problem with PO is, but also who is responsible for it. This research posits that without a reconceptualisation of the problem representation of PO in Australia, Circular Economy outcomes will not be achieved.